2011
DOI: 10.1371/journal.pone.0018227
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Hypertension Severity: Results from a Case-Control Study

Abstract: BackgroundEpidemiologic studies have provided new insights into the association between psoriasis and cardiovascular diseases. Previous population studies have examined hypertension frequency in psoriasis patients. However, the relationship between severity of hypertension and psoriasis has not been characterized.ObjectiveWe sought to investigate whether patients with psoriasis have more difficult-to-manage hypertension compared to non-psoriatic hypertensive patients.ApproachWe performed a case-control study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 28 publications
1
82
0
Order By: Relevance
“…In another retrospective case-control study, psoriasis patients with hypertension were found to have more severe hypertension and required more medications to control blood pressure when compared to the control group [24]. These study results reinforce an important need for dermatologists to routinely screen patients with psoriasis for hypertension.…”
Section: Hypertensionmentioning
confidence: 70%
“…In another retrospective case-control study, psoriasis patients with hypertension were found to have more severe hypertension and required more medications to control blood pressure when compared to the control group [24]. These study results reinforce an important need for dermatologists to routinely screen patients with psoriasis for hypertension.…”
Section: Hypertensionmentioning
confidence: 70%
“…Compared to hypertensive patients without psoriasis, psoriasis patients with hypertension were 5 times more likely to be on a monotherapy antihypertensive regimen, 9.5 times more likely to be on dual antihypertensive therapy, 16.5 times more likely to be on triple antihypertensive regimen, and 19.9 times more likely to be on quadruple therapy or centrally-acting agent in multivariable analysis, after adjusting for traditional cardiac risk factors. Psoriasis patients appear to have more difficult-to-control hypertension compared to non-psoriatic, hypertensive patients (Armstrong et al, 2011).…”
Section: Cardiovascular Diseasementioning
confidence: 92%
“…The pathogenesis of hypertension in psoriasis seems to be linked to increased production of angiotensinogen by adipose tissue, subsequently converted to angiotensin II through angiotensin converting enzyme (ACE) (Armstrong AW et al, 2011).…”
Section: Hypertensionmentioning
confidence: 99%
“…Angiotensin II not only promotes salt retention by kidney but also it regulates vascular tone, acting a vasoconstrictor and stimulates T-cell proliferation promoting inflammation and the development of atherosclerosis (Armstrong AW et al, 2011).…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation